2017
DOI: 10.1111/jocn.13758
|View full text |Cite
|
Sign up to set email alerts
|

An explanatory study on the concept of nursing presence from the perspective of patients admitted to hospitals

Abstract: Knowing the perspectives of patients is important as the evaluation of nursing care quality should rely on outcome indicators that are sensitive to patients. For instance, client satisfaction and health status acceptance, especially as it relates to coping, comfort level, hope, and participation in decision-making, are included in the nursing outcomes' classification system. Thus, the findings of this study may facilitate improvement in the quality of care by continuous improvement in knowledge, attitudes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 38 publications
(55 reference statements)
2
33
0
2
Order By: Relevance
“…Social connections have been found to have strong influences on health (Benzo, ; Holt‐Lunstad, ). However, little attention has been paid to the social interactions between nurses and patients (Mohammadipour, Atashzadeh‐Shoorideh, Parvizy, & Hosseini, ). This meta‐ethnography found that video‐contact and consultations are important to achieve digital proximity.…”
Section: Discussionmentioning
confidence: 99%
“…Social connections have been found to have strong influences on health (Benzo, ; Holt‐Lunstad, ). However, little attention has been paid to the social interactions between nurses and patients (Mohammadipour, Atashzadeh‐Shoorideh, Parvizy, & Hosseini, ). This meta‐ethnography found that video‐contact and consultations are important to achieve digital proximity.…”
Section: Discussionmentioning
confidence: 99%
“…As one participant in Reid et al 's () study noted, perceiving the nurse to be busy led to worry that the nurse would not have time or patience to attend to him/her if needed. This is important as Mohammadipour et al () found that nursing presence alone can be healing factors for consumers who are seriously ill. Others in Reid et al 's () study voiced feeling inhibited from talking freely with the nurse and preoccupied with not wanting to irritate the nurse when he or she appeared busy. Newman et al () noted that some participants in their study interpreted nurses' lack of attention or full presence with consumers as evidence of stigma.…”
Section: Barriersmentioning
confidence: 99%
“…Consumers in acute settings also desire more interaction with their nurses and experience benefit from it (Gaillard et al , ; Shattell et al, ). The therapeutic relationship has also been positively correlated with recovery‐based outcomes such as consumer participation in treatment, coordination of care and collaboration (Mohammadipour et al , ). Consumers also note the importance of empathy among nurses in terms of feeling comfortable approaching them, the importance of nurses trying to understand them, and the attending behaviour of nurses being present (Gerace et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Participants were often left for hours with no follow up care in environments that were either too stimulating or isolated. Being present with a client includes listening, understanding, communicating with and checking on clients while they are receiving care (Mohammadipour, Atashzadeh-Shoorideh, Parvizy, & Hosseini, 2017). A lack of engagement with participants created an environment where they did not feel valued as human beings as they felt their psychosocial needs were unheard and not adequately addressed.…”
Section: Discussionmentioning
confidence: 99%